2011
DOI: 10.1080/10665684.2011.561740
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Perceived Poverty and Academic Achievement on School Counselor Conceptualization

Abstract: This analog study presented 173 practicing school counselors with one of four case scenarios depicting a student new to their school. Each scenario manipulated one of two levels of the independent variables, which were perceived poverty and academic achievement. Main effects indicate that participants rated students as more attractive counseling participants when they are perceived as poor and/or strong academic performers. Implications for school counselors and further research are discussed.Issues of social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 57 publications
1
7
0
4
Order By: Relevance
“…Counselors' training in multiculturalism and diversity, in addition to their knowledge of family life transitions and training in problem solving, provides skills for working with poor students and their families. School counselors also serve a vital role in working at the individual and macro level by removing barriers and inequities that exist within schools (Amatea & West‐Olatunji, ; Griffin & Steen, ; Hutchison, ). By taking an advocacy leadership role, school counselors can voice the need for change and work to develop school and community initiatives (Lee, ).…”
mentioning
confidence: 99%
“…Counselors' training in multiculturalism and diversity, in addition to their knowledge of family life transitions and training in problem solving, provides skills for working with poor students and their families. School counselors also serve a vital role in working at the individual and macro level by removing barriers and inequities that exist within schools (Amatea & West‐Olatunji, ; Griffin & Steen, ; Hutchison, ). By taking an advocacy leadership role, school counselors can voice the need for change and work to develop school and community initiatives (Lee, ).…”
mentioning
confidence: 99%
“…From an equity perspective, this means challenging the status quo and removing barriers that exist for traditionally underrepresented groups of students (i.e., African American, Latino/a, English language learners [ELLs], low-income students). Interestingly, a study by Hutchison (2011) revealed school counselors are more readily advocating for students living in poverty when they are strong academically, versus those who struggle to perform. This study highlighted the school counselor’s propensity to work more closely with students identified from a lower social class; however, when academic motivation was an added variable, there was a notable increase in their attraction to work with students motivated to perform well academically (Hutchison, 2011).…”
Section: School Counselors and Principal Partnership To Advocate Acad...mentioning
confidence: 99%
“…Interestingly, a study by Hutchison (2011) revealed school counselors are more readily advocating for students living in poverty when they are strong academically, versus those who struggle to perform. This study highlighted the school counselor's propensity to work more closely with students identified from a lower social class; however, when academic motivation was an added variable, there was a notable increase in their attraction to work with students motivated to perform well academically (Hutchison, 2011). Therefore, a belief that all students can achieve at a high level is one thing; school counselors' provision of interventions to ensure even those less motivated improve is another.…”
mentioning
confidence: 99%
“…A plethora of research has shown that poverty influences student development in many ways (Howard et al 2011;Williams and Crockett 2013); for example, researchers have found that poverty positively relates to student stress, psychological distress, and poor health choices, especially those involving diet and smoking (Hutchison 2011;Williams and Crockett 2013). In addition, poverty negatively influences student academic achievement.…”
Section: Introductionmentioning
confidence: 97%